The Tactile Quartet: Comparing Ambiguous Apparent Motion in Tactile and Visual Stimuli. (January 2020) - Haladjian, Harry H.; Anstis, Stuart; Wexler, Mark; Cavanagh, Patrick
In the visual quartet, alternating diagonal pairs of dots produce apparent motion horizontally or vertically, depending on proximity. Here, we studied a tactile quartet where vibrating tactors were attached to the thumbs and index fingers of both hands. Apparent motion was felt either within hands (from index finger to thumb) or between hands. Participants adjusted the distance between their hands to find the point where motion changed directions. Surprisingly, switchovers occurred when between-hand distances were as much as twice that of within-hand distances—a general bias that was also found for tactile judgments of static distances. This expansion of within-hand felt distances was again seen when lights were placed on the hands rather than vibrating tactors. Importantly, switchover points were similar when the hands were placed at different depths, indicating that representations governing tactile motion were in perceptual three-dimensional space, not retinal two-dimensional space. This was true whether the quartets were visual stimuli on the hands or were purely visual on a monitor, suggesting that proximity is generally determined in three-dimensional coordinates for motion perception. Finally, the similarity of visual and tactile results suggests a common computation for apparent motion, albeit with different built-in distance biases for separate modalities.